The Conejo Valley Democratic Club Newsletter - Conejo Valley Democratic Club:::::: (1976)
The December 1976 Conejo Valley Democratic Club newsletter announces a New Year's Eve party combined with the election of club officers and presents a proposed slate of candidates. It thanks volunteers for their extensive campaign work in the recent election, highlighting organizing efforts for Carter/Mondale and Tunney and praising local activists by name. An analysis of the State Senate race argues that Sabrina Schiller's loss was due more to weak Democratic performance in Simi Valley and parts of Los Angeles County than in Thousand Oaks. The newsletter promotes a VIP dues program to build grassroots Democratic strength in the 19th Senate District and encourages members to stay active through upcoming conventions and events.